Laparoscopic Nephron-sparing Treatment of Upper Pole Infundibular Obstruction due to Fraley's Syndrome - Joseph M. Armstrong; Samit D. Soni; Richard E. Link (Urology Case Reports, 2016)
Fraley's syndrome results from a rare anatomic variant of the renal vasculature leading to compression of the upper pole infundibulum, caliectasis, hematuria, and flank pain. To date there have been few reported cases in which this condition was treated using a minimally invasive approach. Here, we report a case in which a patient with Fraley's syndrome was successfully treated by performing a laparoscopic YV-infundibulo-pyeloplasty with vasculopexy of a posterior segmental renal artery. Minimally invasive collecting system reconstruction without vascular clamping is feasible, potentially less destructive and offers significant advantages in terms of intraoperative visualization and perioperative patient morbidity.